Allopolyploid speciation in Siberian Dactylorhiza (Orchidaceae, Orchidoideae) - Efimov, Petr G.; Philippov, Evgenij G.; Krivenko, Dennis A. (Phytotaxa, 2016)
Morphological and allozyme analyses of Siberian dactylorchids have revealed the presence of a new, previously undescribed allopolyploid that is described here as species new to science. The genetic constitution as revealed by allozyme analysis of this species confirms that its parents are the diploid Siberian D. fuchsii and D. incarnata, and it is 2n=80, representing the first such count from the Asiatic Russia. In most literature surveys of Siberia, the new species has been identified as D. baltica, which is different in the allele composition of the pgi locus. Morphologically, both allotetraploids are similar; D. sibirica is distinguishable due to the absence of spots on the leaves and a narrower lip with narrower lateral lobes. A brief summary of Dactylorhiza allopolyploids from Siberia (Russia) is presented.